Overweight adolescents and asthma: Revealing motivations and challenges with adolescent-provider communication. (4th March 2018) - Alexander, Gwen L.; Olden, Heather A.; Troy, Tanya; Miree, Cheryl A.; Joseph, Christine L. M.
ABSTRACT: Objective: Among teens with asthma, challenges of disease management may be greater in those with a body mass index (BMI) >85th percentile compared to youth within the parameters for normal weight-for-age. This mixed-methods study assessed teens' awareness of the link between weight and asthma management, and perspectives on how medical providers might open a discussion about managing weight. Method: Teens aged 13–18, having BMI >85 percentile and chronic asthma, identified using health system databases and a staff email message board, were invited to complete a semi-structured, in-depth phone interview. Interviews were audio taped, transcribed, and qualitatively analyzed, using the Framework Method. Responses were summarized and themes identified. Descriptive summaries were generated for a 16-item survey of weight conversation starters. Results: Of 35 teens interviewed, 24 (69%) were girls, 11 (31%) boys, 20 (63%) African-American. All teens reported having "the weight conversation" with their doctors, and preferred that parents be present. Half knew from their doctor about the link between being overweight and asthma, others knew from personal experience. Nearly all expressed the importance of providers initiating a weight management conversation. Most preferred conversation starters that recognized challenges and included parents' participation in weight management; least liked referred to "carrying around too much weight." Conclusions: Most teens responded favorably to initiating weight loss if it impacted asthma management, valued their provider addressing weight and family participation in weight management efforts. Adolescents' views enhance program development fostering more effective communication targeting weight improvement within the overall asthma management plan.